Malignant and benign sinonasal paragangliomas. (31st January 2013) - Papaspyrou, Konstantinos; Welkoborsky, Hans‐Juergen; Gouveris, Haralampos; Mann, Wolf J.
Abstract : Objectives/Hypothesis: To report on the clinical course and management of sinonasal paragangliomas (PGLs). Study Design and Methods: Retrospective chart review of six patients with PGLs of the nasal cavity and paranasal sinuses. Results: Three patients had tumors with malignant clinical behavior with cerebral metastases or infiltration of brain and local recurrence, despite surgery and/or radiotherapy, while three patients demonstrated a benign course. Conclusion: Sinonasal paragangliomas are frequently malignant. If malignant, they are very aggressive, with rapid local spread as well as high metastatic potential despite surgical resection; and they have a poor prognosis. Malignancy cannot be diagnosed on histology, but only on the basis of clinical behavior. Intracranial metastasis is commonly expected. Long‐term follow‐up, with particular emphasis put on the intracranial structures, is mandatory as recurrences or metastasis may occur even after a long time interval. Level of Evidence: 4. Laryngoscope, 123:1830–1836, 2013